Об устойчивости приближенных решений нечетких дифференциальных уравнений в пространстве E2 - Слынько, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The stability of solutions of differential equations in the E2 space is investigated. The Lyapunov unction is constructed by using the classical isoperimetric Brunn-Minkowski inequality.